State-of-the-art methodologies to identify antimicrobial secondary metabolites in soil bacterial communities-A review. (August 2020) - Dror, Barak; Jurkevitch, Edouard; Cytryn, Eddie
Abstract: Non-ribosomal peptides (NRPs) and polyketides (PKs) are among the most profuse families of secondary metabolites (SM) produced by bacteria. These compounds are believed to play an important ecological role in microbe-microbe and microbe-plant interactions in soil and roots microbiomes. Over the years, screening of NRPs and PKs in soil bacteria has resulted in high rates of rediscovery, mainly due to challenges associated with bacterial isolation. The quest to expose compounds in the hidden "unculturable" fraction of the soil microbiome, and to activate existing and novel SM gene clusters in cultivated bacteria, has facilitated a paradigm shift from traditional isolation-based natural product identification platforms to novel 'ecologically inspired' culturing techniques and cutting-edge culture-independent methods. This review provides a comprehensive overview of platforms and applications for studying secondary metabolites in soil and root environments, deliberating the benefits and limitations of the various approaches. Initially, it highlights innovative methodologies to "culture the unculturable" to uncover novel soil bacterial SM. Next, it explores "culture-independent" platforms for the identification of SM-synthesizing gene clusters through next generation sequencing and bioinformatics. It then evaluates innovative approaches for heterologous expression of metabolites from complex soil environments. Finally, it presents a conceptual integrated pipeline for evaluating the potential function and role of root-associated bacterial SM in suppressive soils that inhibit plant pathogens. This pipeline can be modified to address the ecological role of SM in other soil and root ecosystems, which can ultimately enhance our understanding of microbe-microbe and bacterial-plant interactions. Highlights: Soil microbiomes harbor a myriad of ecologically-important non-ribosomal peptides (NRPs) and polyketides (PKs). There is a research gap in understanding the environmental function of these metabolites in soil and roots. We propose a conceptual pipeline for characterizing novel NRPs and PKs.